Moutains of fire - Rosenfeld, Michael; Alfieri, Mary (Washington, D. C. : National Geographic Society, 1989)
The video shows a volcanic eruption
The video was recorded from the National Geographic Special aired on TV3
Copy available in DVD format
Keywords: Volcanic ash, tuff, etc; Volcanoes